The impact of economic and behavioural factors on the shaping of international relations with the Russian Federation. A comparative analysis of Poland and Germany - Motowidlak, Tomasz; Motowidlak, Urszula (Publishing House of Wroclaw University of Economics and Business, 2024)
Research background: The article addressed the importance of economic and behavioural factors in shaping relations between states. This significance was examined in the context of the possibility of building the power and strength of the state, ensuring economic security, and in particular energy security. Purpose of the article: The aim of the article was to identify the main economic and behavioural dependencies of the diverse attitudes of Poland and Germany towards the Russian Federation, and to determine the impact of these dependencies on these attitudes. Methods: The research methods and techniques included: elementary analysis, desk research, cause-and-effect analysis, and selected qualitative and quantitative analysis methods. Findings and value added: The obtained results are important for international political economy and geoeconomics. The study covered the economic and behavioural factors determining the relations between Poland and the Russian Federation as well as those between Germany and the Russian Federation. The results of the comparison of these two categories of bilateral relations explain the different attitudes of Poland and Germany towards the Russian Federation, which was particularly visible in the context of the Russian aggression against Ukraine and contribute to reducing the research gap in this thematic area.
Argumenta Oeconomica, 2024, Nr 2 (53), s. 120-129
Keywords: Polish-Russian relations; German-Russian relations; economic and behavioural factors in shaping international relations; Russian Federation; international political economy